DEVELOPMENT OF MOBILE MICRO-LEARNING USING TIKTOK TO ENHANCE DIGITAL LITERACY FOR UNDERGRADUATE STUDENTS - Pattaravindechopat, Natthanan; Siripipattanakul, Sutithep (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this research were: 1) to develop Mobile Micro-learning using TikTok to enhance digital literacy for undergraduate students 2) to compare digital literacy of undergraduate students before and after learning with Mobile Micro-learning using TikTok and 3) to study undergraduate students satisfaction toward Mobile Micro-learning using TikTok to enhance digital literacy. The sample group consisted of 29 undergraduate students in the Bachelor of Physical Education using cluster sampling. The research tools were as follows: 1) 5 Lesson plans 2) Mobile Micro-learning multimedia using TikTok to enhance digital literacy for undergraduate students. 3) Digital literacy test used in pre-study and post-study tests. 4) Undergraduate students' satisfaction survey toward Mobile Micro-learning using TikTok to enhance digital literacy. The results of the study found that; 1) The quality of Mobile Micro-learning media using TikTok to enhance digital literacy showed an overall high level of quality. 2) Post-learning test scores of undergraduate students were significantly higher than Pre-learning test scores at a statistical significance level of .01. 3) The satisfaction survey results of undergraduate students towards Mobile Micro-learning using TikTok to enhance digital literacy showed an overall high level of satisfaction.